Studying the Chemical Components and Bioactivities of Rhodomyrtus Tomentosa Extracts - Thi Viet Huong, Do (VNU Journal of Science: Natural Sciences and Technology; Vol 35 No 1, 2019)
Rhodomyrtus tomentosa is a flowering plant belonging to the family of Myrtaceae. This paper uses Rhodomyrtus tomentosa leaves as the sample of the study. Three compounds: hodomyrtosone, combretol and loliolide, were isolated from n-hexan extract (RTH); their structures were identified with proton and carbon-13 NMR spectra. The determining of the total flavonoids (TF) and phenolic (TP) content shows that the ethylacetate extract has higher value for both TF and TP (25.32 mg BHT/g; 60.01 mg GAE/g) compared with the n-hexan extract.  Keywords   Rhodomyrtus tomentosa , rhodomyrtosone, combretol, loliolide, total flavonoids content, total phenolic content. References [1] S. Csurhes, C. Hankamer Ceylon Hill Cherry (DownyRose Myrtle): Rhodomyrtus tomentosa. Brisbane, Queensland, Australia: Biosecurity Queensland, 2016. [2] T.L. Do, Medicine Plants and Remedies of Vietnam. Hanoi: Thoi Dai publisher, 2004, 434. [3] V. Arya, A review on anti tuberculosis plants. Int. J. PharmaTech. Res., vol 3(2) (2011) 872-880. [4] H. Ong, M. Nordiana, Malay ethno‑medico botany in Machang, Kelantan, Malaysia. Fitoterapia, vol. 70(5) (1999) 502‑13. [5] F. Wei, Manufacture of Oral Liquid Containing Traditional Chinese Medicine Extract for Treating Gynecopathy (Guangxi Huahong Pharmaceutical Co., Ltd., People’s Republic of China; Shanghai Fosun Pharmaceutical (Group) Co., Ltd.), Faming Zhuanli Shenqing Gongkai Shuomingshu. People’s Republic of China Patent CN1846715, 2006. [6] W. Chuakul, Medicinal plants in the Khok Pho district, Pattani province (Thailand). Thai J. Phytopharm, vol. 12 (2005) 23‑45. [7] T. Lim, Rhodomyrtus tomentosa. Edible medicinal and non medicinal plants. New York: Springer, 732‑7, 2012.7 [8] K.M. Geetha, C.Sridhar, V. Murugan, Antioxidant and Gastroprotective activities of Rhodomyrtus tomentosa (Ait.) Hassk. International Journal of PharmTech Research, vol 2 (1) (2010) 283-291. [9] D. Jeong, W. S. Yang, Y. Yang, G. Nam, J. H. Kim, D. H. Yoon, H. J. Noh, S. Lee, T. W. Kim, G. Sung, J. Y. Cho, In vitro and in vivo anti-inflammatory effect of Rhodomyrtus tomentosa methanol extract. Journal of Ethnopharmacology, vol. 146 (2013) 205-213. [10] G. Lavanya, S. P. Voravuthikunchai, N. H. Towatana, Acetone extract from Rhodomyrtus tomentosa: A potenr natural antioxidant. Evidence Based Complementary and Alternative Medicine, vol. 10 (2012) 1155-5. [11] T. N. H. Lai, C. André, H. Rogez, E. Mignolet, T. B. T. Nguyen, Y. Larondelle, Nutritional composition and antioxidant properties of the simfruit (Rhodomyrtus tomentosa). Journal of Food Chemistry, vol. 168 (2014) 410-426. [12] T. N. H., Lai, M. Herent, J. Quentin-Leclerq, T.B. T. Nguyen, H. Rogez, Y. Larondelle, C. M. André Piceatannol, a potent bioactive stilbene, as major phenolic component in Rhodomyrtus tomentosa. Journal of Food Chemistry, vol. 138 (2012) 1421-1430. [13] C. Cui, S. Zhang, L. You, J. Ren, W. Luo, W. Chen, M. Zhao, Antioxidant capacity of anthocyanins from Rhodomyrtus tomentosa (Ait.) and identification of the major anthocyanins. Journal of Food Chemistry, vol. 139 (2013) 1-8. [14] X. Wu, G.R. Beecher, J.M. Holden, D.B. Haytowitz, S.E. Gebhardt, R.L. Prior, Lipophilic and hydrophilic antioxidant capacities of common foods in the United States. J Agric Food Chem, vol. 52(12) (2004) 4026‑37. [15] S. Limsuwan, A. Hesseling‑Meinders, S.P. Voravuthikunchai, J.M. Van Dijl, O. Kayser. Potential antibiotic and anti‑infective effects of rhodomyrtone from Rhodomyrtus tomentosa (Aiton) Hassk. on Streptococcus pyogenes as revealed by proteomics. Phytomedicine, Vol 18(11) (2011) 934‑40. [16] D. Marinova, F. Ribarova, Altanassova. Total phenolics and total flavonoids in Bulgarian fruits and vegetables. Journal of The University of Chemical Technology and Metallurgy, vol 40 (2005) 255-260. [17] Dachriyanus, Salni, M.V. Sargent, B. W. Skelton, I. Soediro, M. Sutisna, A. H. White, E. Yulinah. Rhodomyrtone, an antibiotic from Rhodomyrtus tomentosa. Aust. J. Chem, Vol. 55 (2002) 229-232. [18] Dachriyanus, R. Fahmi, M.V. Sargent, B. W. Skelton, A. H. White, E. Yulinah, 5-Hydroxy-3,3’,4’,5’,7-pentamethoxyflavone (combretol). Acta Cryst.,, Vol. E60 (2004) 86-88. [19] R. Hoges, A.L. Porte, The structure of loliolide: A terpene from Lolium perenne. Tetrahedron, Vol. 20 (1964) 1463-1467. [20] J. Kimura, N. Maki, New loliolide derivatives from the brown alga Undaria pinnatifida. J. Nat. Prod., Vol 65 (2002) 57-58. [21] https://www.psychologytoday.com/us/articles/200307/flavonoids-antioxidants-help-the-mind. [22] https://www.nutraingredients.com/Article/2008/10/10/Flavonoids-heart-health-benefits-in-the-blood-vessels-Study.